PERTENTANGAN DAN PERGUMULAN SYI’AH DI INDONESIA DALAM TRAGEDI SAMPANG - Qodir, Zuly (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
Studies on Shiites in Indonesia has become a serious problem related to the political issues. The existence of Shiite treated less sympathetically by other Islamic groups. This paper was based on a literature review and as well as the opinions expressed by the Indonesian Muslim leaders associated with the Shiites in Indonesia, particularly in Sampang, Madura. The approach in this paper was a political sociology, not theological. The focus of this study, first, explores the difference between Shiite and Sunni Muslims; second, to understand the cause of conflict between Shiite and Sunni Muslims. The findings of this study confirms, there was a difference between Sunnis and Shiites in some aspects. But it must be stressed, the cause of the conflict between Shiites and Sunnis not a theological issue, but a political problem. however, political issues were brought to the theological issues that cause conflicts and clashes such as the case of Sampang.